2016
DOI: 10.4103/0973-1229.193079
|View full text |Cite
|
Sign up to set email alerts
|

Neural Implications of Psychotherapy, Pharmacotherapy, and Combined Treatment in Major Depressive Disorder

Abstract: Numerous clinical trials have been conducted to determine the utility of antidepressant treatment (ADT), psychotherapy, and combined psycho-pharmaco-psychotherapy (PPPT) in treating major depressive disorder (MDD). While all approaches have shown benefit over placebo to varying degrees, the parallel neurophysiological mechanisms that underlie their efficacy have received little attention. The authors will review and discuss a growing body of literature that relates the factors of treatment selection and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Empowering positive psychology concepts such as optimism and hope can reduce poor functioning and promote behavioral adaptation. Results reported here are in line with Schwartz and Santarsieri [43] who reported that combining antidepressant treatment and psychotherapy (psycho-pharmaco-psychotherapy or PPPT) created potentially ob- servable neurofunctional changes. They suggested that the sum of these effects in PPPT may produce more sustained symptom relief.…”
Section: Relation Between Tdcs and Ppsupporting
confidence: 92%
“…Empowering positive psychology concepts such as optimism and hope can reduce poor functioning and promote behavioral adaptation. Results reported here are in line with Schwartz and Santarsieri [43] who reported that combining antidepressant treatment and psychotherapy (psycho-pharmaco-psychotherapy or PPPT) created potentially ob- servable neurofunctional changes. They suggested that the sum of these effects in PPPT may produce more sustained symptom relief.…”
Section: Relation Between Tdcs and Ppsupporting
confidence: 92%
“…If not improved, antidepressant drugs and combined psychotherapy are taken later. As for severe depression, it may need a combination of antidepressants and antipsychotics, antidepressants, and psychotherapy or electroconvulsive therapy [ 16 ]. As for short-term treatment, benzodiazepines are recommended if the patient suffers from acute suicidal depression, catatonic depression, or depression with symptoms, such as insomnia and anxiety [ 17 ].…”
Section: Discussionmentioning
confidence: 99%